Survey on the Use of Digital Innovation for SMEs During the COVID-19 Pandemic in Indonesia - Amalia, Lutfi; Juhary, Ali (2023)
One of ASEAN's most important economies is Indonesia. According to data on Indonesia's GDP (Gross Domestic Product) provided by the ASEAN Secretariat, the country's GDP was US$ 1.01 trillion, or Rp. 14,837 trillion in 2018. Development of Small, Micro, and Medium Enterprises Unit is one of Indonesia's policies to boost economic growth (SMEs). However, SMEs were the industry most impacted by the Large-Scale Social Restrictions during the COVID-19 epidemic (PSBB). At that time, SMEs had trouble meeting their productivity goals. As a result, the shift from offline to online consumption of public goods and services. Many SMEs continue to grow their operations using conventional technology simultaneously. So, it is clear that there is a need to expand the proportion of SMEs using digital innovation. As a result, the author examines how SMEs in Indonesia use digital innovation to show that advantageous to SMEs' ability to continue producing goods and services.